Covid-19 disease effect on diabetic foot ulcer management, a big challenge in its management: A case report & literature review - Hassani, Mohammad; Salajeghe, Samira; Nozarinia, Mustafa; Salajeghe, Sara (Researcher Bulletin of Medical Sciences, 2022)
Covid-19, which is now pandemic in countries around the world, including Iran. It has shown to cause hypoxia, which can lead to impaired wound healing. In positive covid-19 patients, the patient and his companion’s do not usually do appropriate washing of wounds. In addition, economic issues such as procurement and mask of personnel exposed to the patients with covid-19 disease are also an issue. In this article, Corona suspicious patient presented with a diabetic foot and required hospital admission. As such a patient with specific condition suspicion was required to admit, we needed to create a guideline for him and for upcoming similar cases. The patient was a 74-year-old diabetic man who did not respond to debridement. So the patient underwent below-knee amputation, which ended up to above the knee amputation due to a Klebsiella infection and failure to respond to non-invasive treatment of wound infection of stump of below-knee amputation and the patient’s condition. The question is whether Corona- related hypoxia has exposed the patient to nosocomial infection, or the patient’s lack of self-control at home as well as the medical staff lack of care due to fear of corona was the reason? In the period of the patient was under treatment, there was no significant complaint of shortness of breath. Conclusion: in patent with diabetic foot and covid-19 suspicion _ especially in critically ill patient may benefit from aggressive approach such as early major amputation because of cost-benefit and minimizing covid-19 risk must consider.